Volume 7B: Structures and Dynamics 2014
DOI: 10.1115/gt2014-25648
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-Induced Vibration and Frequency Lock-In of an Airfoil at High Angles of Attack

Abstract: Vortex-induced vibration is a fluid instability present in many areas, including offshore platforms, wind turbines, and turbomachinery. The vortices due to secondary flows exert an periodic unsteady force on the elastic structure, leading to potentially dangerous vibrations. Under certain circumstances, the shedding frequency can lock into the structure natural frequency and lead to limit cycle oscillations. These high amplitude vibrations can cause material fatigue, and are a common source of structural failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The angle of attack is 40 • and the Reynolds number is 100,000 (U = 5.8 m/s). Figure 9d and other comparable data may be found in Besem et al [51]. The diamond symbols represent conditions where the shedding and enforced frequencies are unlocked, the circle symbols show lockin conditions, and the square symbols have a chaotic behavior that can be attributed to the edge of the lock-in region.…”
Section: Correlation Analyses For Frequency Lock-in Regionsupporting
confidence: 82%
“…The angle of attack is 40 • and the Reynolds number is 100,000 (U = 5.8 m/s). Figure 9d and other comparable data may be found in Besem et al [51]. The diamond symbols represent conditions where the shedding and enforced frequencies are unlocked, the circle symbols show lockin conditions, and the square symbols have a chaotic behavior that can be attributed to the edge of the lock-in region.…”
Section: Correlation Analyses For Frequency Lock-in Regionsupporting
confidence: 82%
“…These conclusions came from utilizing POD methods to create a ROM, which can predict results faster and as accurate as full computational models, requiring at least two degrees of freedom and two harmonics. In addition, Besem and Tang performed experimental studies on the lock-in region for a NACA 0012 airfoil [92]. They found that the lock-in region to experiments is wider, capturing the chaotic edge region between locked and unlocked.…”
Section: Aerodynamic Lco: Buffet Aws and Nsvmentioning
confidence: 99%
“…22. The potential "lock-in" phenomenon is a feature of NSV, which can be referred to the related phenomena in vortex-induced vibrations [23][24][25] that occurred in the cross-flow of a bluff body or a streamlined body at a high angle of attack. In vortexinduced vibrations, when the vortex shedding frequency is close to the body oscillation frequency, it may "jump" to the oscillation frequency, and the vibration amplitude will significantly increase.…”
Section: Introductionmentioning
confidence: 99%